Capacity Building Challenges and Strategies in the Development of New Capital City of Indonesia (Jurnal Bina Praja, 2023)
This study aims to analyze the challenges faced in preparing capacity building in the context of the development of the new capital city of Indonesia and identify strategies that can be implemented to overcome these challenges. This study uses a qualitative approach by analyzing data from secondary sources, such as official government documents, research reports, and related publications. The analysis tool that is maximized is NVivo 12 Plus. The results showed that several challenges must be overcome in preparing the capacity building for developing the new capital city (IKN). These challenges include limited skilled human resources, budgetary constraints, gaps in knowledge and skills, coordination and collaboration between stakeholders, technological change, and innovation. These challenges affect the effectiveness and efficiency of development, as well as the sustainability of the development of the new capital city. In overcoming these challenges, the recommended strategy includes the government's commitment to providing adequate resources, developing supportive policies, and close cooperation between all relevant stakeholders. In addition, a participatory, inclusive, and sustainable approach is considered important to ensure the success of capacity building. Through the involvement of all parties, recognition of the needs and aspirations of the community, and the use of a sustainable approach, the development of the new capital city can run well and provide sustainable benefits for local communities.
Keywords: capacity building; sustainable development; new capital city; urban development